The electrochemical reduction of hydrogen peroxide on a palladium-amorphous carbon composite in an alkaline medium - Jelena Čović; Valentin Mirčeski; Aleksandra Zarubica; Aleksandar Bojić; Miloš Marinković; Marjan Ranđelović (Macedonian Journal of Chemistry and Chemical Engineering, 2023)
The study of hydrogen peroxide reduction in an alkaline aqueous medium on a composite of palladium particles dispersed in an amorphous carbon matrix (Pd@AC) was performed. Scanning Electron Microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), Fourier-transform infrared spectroscopy (FTIR), and X-ray Powder Diffraction (XRD) were used to examine morphology, composition, and crystalline structure. The crystalline structure and size of palladium were analyzed using XRD. The reduction of hydrogen peroxide was studied through cyclic and square-wave voltammetry in an alkaline solution in the absence and presence of dissolved oxygen. The overall electrocatalytic effect of Pd@AC toward hydrogen peroxide reduction strongly depends on the presence of oxygen and the hydrogen peroxide disproportionation reaction in the three-phase system of amorphous carbon, palladium particles, and electrolyte solution.